Early Identification of Proteinuria by Using Urine Dipstick among Patients with Type II Diabetes in Selected Community Area, Kanchipuram Dist., Tamil Nadu, India (Medico Legal Update, 2020)
Early identification of Proteinuria by using urine dipstick among patients with Type II Diabetes inSelected Community Area, Kanchipuram Dist, Tamil Nadu, India. The objectives of the study to assessthe Proteinuria by using urine dipstick among Patients with Type II Diabetes. To find out the associationbetween level of Proteinuria with selected demographic variables among Patients with Type II Diabetes..The sampling technique was non probability- purposive sample technique and the sample size was 200. Thedemographic variable proforma and the random urine dipstick analysis were done to identify the prevalenceof proteinuria. The interpretations were nil, trace, 1+, 2+ and 3+.. Hypothesis were formulated. The level ofsignificance selected was p